Resilience and Vulnerability in Urban Water Distribution Networks through Network Theory and Hydraulic Simulation. (2015) - Soldi, Davide; Candelieri, Antonio; Archetti, Francesco
Abstract: Resilience and vulnerability of networked infrastructures are strictly linked: while resilience is focused on a general evaluation of the robustness of the entire infrastructure, vulnerability is associated with a specific component, or set of components, to represent the possibility of being influenced by hazards/threats and the severity of the possible consequences. In the proposedframework, complex network theory is used to evaluate resilience and vulnerability of a WDN (structural connectivity)whilehydraulic simulation (EPANET) is adopted to estimate the potential stress on pipes according to the level of service of the WDN. The aim is to provide a decision support functionality to assist the definition of intervention planbyrankingpipes according to integrated information on vulnerability/resilience and hydraulic stress. The proposed framework, developed within the ICeWater project, has been evaluated on both benchmark and two real world WDNs (pilots in Timisoara and Milan), starting from their hydraulic software models.